The Impact Of Big Data Analytics On Management Accounting Information Quality And Decision-Making: A Field Study On Saudi Listed Companies - Almushaiqeh, Abdulrahman T.; Abukhashabah, Abdulaal H.; Mufti, Mohammed H. (Journal of Posthumanism, 2024)
This study primarily aimed to examine the availability of Internal and External Big Data in Saudi listed companies on the main market. It also investigated the impact of Big Data Analytics (BDA) on Management Accounting Information Quality (MAIQ) and decision-making. An inductive approach was adopted through a review of relevant literature, alongside descriptive and diagnostic analyses to assess respondents’ perspectives and to test the main and sub-hypotheses. The findings revealed a statistically significant impact of BDA in enhancing both the fundamental and secondary characteristics of MAIQ, thereby supporting more effective operational and investment decisions. Based on the results, the study recommends investing in digital infrastructure, developing data analytics skills among management accountants, integrating internal and external Big Data (BD) sources, and fostering a data-driven decision-making culture. Finally, it emphasizes the need for future research on the role of artificial intelligence (AI) in advancing the quality of management accounting information.